Penerapan Keamanan Pangan di Street Food: Tinjauan Sistematis : Food Safety Implementation in Street Food: A Systematic Review - Venaprilla, Syarifa Gadis; Khabibi, Arsila; Syafitri, Anzilika Avia; Septa Indra Puspikawati (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2026)
Background: Food safety is a pressing global public health issue, as contaminated food can cause millions of illnesses each year. Street food is an important segment of the food industry, providing ready-to-eat food at affordable prices and easy access. However, because this sector is largely informal and lacks regulatory oversight, the potential for food safety risks is high, particularly in developing countries. Objectives: To present a systematic review of food safety practices in street food globally from 2020 to 2025. Methods: This systematic review followed the PRISMA 2020 guidelines with narrative synthesis. A literature search was conducted in March 2025 using three databases, ScienceDirect, Google Scholar, and PubMed, using a combination of keywords with boolean operators. A total of 9 studies meeting the inclusion criteria were analyzed thematically. Study quality was assessed using the JBI Critical Appraisal Tool. Results: Studies have shown that lack of formal training, inadequate supervision, and poor hygiene conditions are the main factors increasing the risk of food contamination. Although vendors' experience and environmental cleanliness can improve food safety practices, these are insufficient without strict regulations and continuous training. Conclusions: Efforts to improve food safety must involve a comprehensive approach, including ongoing training, good regulation, provision of appropriate infrastructure, and increased awareness among traders and consumers.